Pengaruh Model Pembelajaran Inkuiri terhadap Pemahaman Konsep Anatomi Tumbuhan pada Mahasiswa Pendidikan Biologi - Enggar Hadi Wibawa; Maria Octaviana; Ruth Dewayanti (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
Conceptual understanding of plant anatomy is crucial for prospective biology teachers, yet it is often hindered by lecture-dominated teaching methods and limited inquiry-based laboratory experiences. Specifically, students frequently struggle to connect microscopic structures with their functions, resulting in suboptimal conceptual mastery. This study aims to analyze the effect of the inquiry learning model on students’ understanding of plant anatomy concepts in a Biology Education program. The novelty of this research lies in its focus on plant anatomy at the higher education level for pre-service teachers, the integration of multiple-choice questions with reasoning and essay tests, and the combined evaluation of conceptual gain and statistical significance. A quantitative approach was employed using a quasi-experimental pretest–Posttest control group design. The sample consisted of 60 students, divided into an experimental class (inquiry-based, n=30) and a control class (conventional, n=30) through purposive sampling. Instruments were validated by experts and tested for reliability. Data analysis included normality and homogeneity tests, paired and independent samples t-tests, as well as normalized gain (N-Gain) analysis. The results revealed that the experimental class achieved a higher Posttest mean score (82.7) compared to the control class (71.2), with N-Gain scores of 63.9% (high category) versus 40.2% (medium category), and a significant difference (p < 0.05). These findings confirm that the inquiry model significantly enhances conceptual understanding of plant anatomy. In conclusion, inquiry-based learning is effective in strengthening students’ conceptual understanding and is recommended for plant anatomy courses to support the pedagogical readiness of future biology teachers.